2016
DOI: 10.1051/matecconf/20166706010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on CO2-Brine-Rock Interaction of Enhanced Geothermal Systems with CO2as Heat Transmission Fluid

Abstract: Abstract. Enhanced Geothermal Systems (EGS) with CO 2 instead of water as heat transmission fluid is an attractive concept for both geothermal resources development and CO 2 geological sequestration. Previous studies show that CO 2 has lots of favorable properties as heat transmission fluid and also can offer geologic storage of CO 2 as an ancillary benefit. However, after CO 2 injection into geological formations, chemical reaction between brine and rock can change chemical characteristics of saline and prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We elected to adopt a 5-spot well pattern because of its wide application in oil fields and geothermal reservoirs [3,9,[17][18][19][20][21][22]. The resulting 3D model domain with its 5-spot well pattern is illustrated in Figure 1.…”
Section: D Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…We elected to adopt a 5-spot well pattern because of its wide application in oil fields and geothermal reservoirs [3,9,[17][18][19][20][21][22]. The resulting 3D model domain with its 5-spot well pattern is illustrated in Figure 1.…”
Section: D Model Setupmentioning
confidence: 99%
“…Several recent experimental and numerical efforts quantify geochemical reactions associated with CO 2 injection in EGS reservoirs [2,3,[5][6][7][8][9][10]. Pruess [2,3] compared CO 2 and water with respect to heat extraction rate and mass flow rate in EGS reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when considering the wellbore frictional pressure losses, the CO 2 -EGS would be less effective at energy extraction than a water-EGS for conditions used in past EGS trials. Xu et al numerically studied the fluid-rock interactions in the periphery using one-dimensional and twodimensional models and CO 2 as the EGS working fluid, and showed that the dissolved CO 2 diffusing to the periphery of the EGS zone dissolved primary minerals with precipitation of secondary carbonate and clay minerals, which resulted in significant CO 2 being trapped in the rock matrix, a condition that is favorable for geological storage [127,128]. Xu et al numerically studied the fluid-rock interactions in the periphery using one-dimensional and twodimensional models and CO 2 as the EGS working fluid, and showed that the dissolved CO 2 diffusing to the periphery of the EGS zone dissolved primary minerals with precipitation of secondary carbonate and clay minerals, which resulted in significant CO 2 being trapped in the rock matrix, a condition that is favorable for geological storage [127,128].…”
Section: Field-scale Numerical Simulation Of Co 2 -Egsmentioning
confidence: 99%
“…In addition, it was suggested that a CO 2 -EGS would be better than a water-EGS in lower permeability reservoirs and with the use of larger wellbores [125,126]. Xu et al numerically studied the fluid-rock interactions in the periphery using one-dimensional and twodimensional models and CO 2 as the EGS working fluid, and showed that the dissolved CO 2 diffusing to the periphery of the EGS zone dissolved primary minerals with precipitation of secondary carbonate and clay minerals, which resulted in significant CO 2 being trapped in the rock matrix, a condition that is favorable for geological storage [127,128]. Luo et al numerically investigated a doublet CO 2 -EGS system based on conditions at the European EGS site at Groβ Schönebeck using the CFD code FLU-ENT 6.3, including dramatic variations of the supercritical CO 2 properties and the thermal-hydraulic turbulence features of CO 2 in the wellbores [120].…”
Section: Field-scale Numerical Simulation Of Co 2 -Egsmentioning
confidence: 99%